Contemporary artificial intelligence - Neapolitan, Richard E.; Jiang, Xia, 1967- (Boca Raton, Fla. : Taylor & Francis, 2013)
"A thorough introduction to artificial intelligence (AI), this text provides a comprehensive and in-depth overview of the key concepts and techniques in AI. It also discusses the various areas and successes of the rational and emergent software approaches to AI. Throughout the text, theory is introduced via examples, giving readers the foundation to solve problems with logic that they can use later in AI-related research and other domains. The author also covers algorithms in sufficient detail, allowing readers to readily understand and implement them"--
Includes bibliographical references and index.
Keywords: Artificial intelligence; COMPUTERS / Machine Theory; COMPUTERS / Software Development & Engineering / Systems Analysis & Design; TECHNOLOGY & ENGINEERING / Electronics / General